PENGARUH METODE THINK PAIR SHARE DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM KELAS III SD PONTIANAK - Jimmi Susanto; Tahmid Sabri; Hery Kresnadi (Universitas Tanjungpura, 2020)
AbstractThis study aims to analyze the effect of the use of Think Pair and Share methods on student learning outcomes in learning Natural Sciences class III SD Negeri 55 West Pontianak. The method used is the Experimental Method. In this study the study used a Quasi Experimental design in the form of Nonequivalent Control Group Design. The population in this study were all grade III students of the 55 Pontianak Elementary School in West Pontianak, while the sample was obtained by drawing in all class III. Based on the draw, the research samples were class III A (Experiment class) and III B (Control class) of 70 students. Data collection techniques used are direct observation techniques and measurement techniques as well as data collection tools used in the form of observation sheets and test deeds. Based on the analysis of the data obtained the average results of the experimental class post-test of 72.83 and 68.56 control class post-test, obtained tcount = 2.497 at a significant level (α) = 5% dk numerator = (36 + 34) - 2 = 68 obtained ttable = 1.9973 thus tcount> ttable, then Ha is accepted. So, it can be concluded that there is an influence of the use of Think Pair and Share methods on student learning outcomes in learning Natural Sciences class III SD Negeri 55 West Pontianak. Based on the results of the calculation of the effect size obtained effect size = 0.506. This value is in the medium category. This shows that learning using the Think Pair and Share method has a moderate effect on learning science in class III 55 Pontianak Primary School. Keywords: Learning Method, Think Pair Share